Exploring uplift modelling in direct marketing - Mayes, Cindy-Lee; Govender, Krishna K (Goodwood Publishing, 2019)
Purpose: This research examines the importance of an uplift marketing model compared to traditional response models, used in direct marketing. Research Methodology: A multi-method research approach was used which included a survey using an electronic questionnaire and a semi-structured interview. Results: The research findings reveal that the value of employing uplift models in direct marketing. is that it factors change in behaviour from the action, which traditional response models do not. Limitation: The study was conducted in a single institution and focused only on scustomers with banking needs. Contribution: By employing an uplift model in direct marketing it is possible to increase marketing return-on-investment and positively impact brand loyalty and brand perception. Thus, marketers need to be cognizant of these findings and strategize accordingly. Keywords: Direct marketing, Customer management, Marketing model, Marketing communication